A Comparative Analysis of Adaptive Notch Filtering and Wavelet Mitigation against Jammers Interference. Issue 4 (December 2016) - Musumeci, Luciano; Curran, James T.; Dovis, Fabio
Abstract: Global Navigation Satellite System (GNSS) receivers are vulnerable to the threats of unintentional interference generated by other communication systems and intentional interference known also as jamming. In particular, the intentional transmission of Radio Frequency (RF) interference with the goal of disrupting one or more of the received GNSS frequency bands can disrupt the operation of GNSS receivers over a wide target area. This paper provides a comparison between two interference mitigation techniques at the digital signal processing level. The traditional adaptive notch filtering has been compared with a more innovative technique based on the use of the Wavelet Packet Decomposition (WPD). Using simulated GNSS jammed scenarios and a software‐defined GNSS receiver, results indicate the benefits of WPD relative to notch filtering. Further tests using love interference signals, and both a software and commercial hardware receiver, demonstrate the benefits of WPD in terms of signal quality and position domain metrics. Copyright © 2016 Institute of Navigation Copyright © 2017 Institute of Navigation